Intimacy and mobility in an era of hardening borders : Gender, reproduction, regulation - Pine, Frances, 1952-; Haukanes, Haldis (Rethinking borders (Manchester, England), 2021)
Based on vivid and illuminating ethnographic research from both east and west Europe, this book investigates the relationship between geopolitical and physical borders and ideological, classificatory boundaries, highlighting bordering process, and showing how the two often operate in tandem in the regulation of reproduction, care and intimacy.